Multiethnic meta-analysis identifies ancestry-specific and cross-ancestry loci for pulmonary function - Annah B. Wyss (Nature Portfolio, 2018)
Pulmonary function is influenced by environmental factors, lifestyle, and genetics. Here, in a multiethnic GWAS meta-analysis for pulmonary function traits, the authors identify over 50 additional genetic loci, a subset of which are specific for European, African, Asian, or Hispanic/Latino ancestry.